Can mycophenolate mofetil be tapered safely in myasthenia gravis? A retrospective, multicenter analysis. Issue 2 (18th June 2015) - Hobson‐Webb, Lisa D.; Hehir, Michael; Crum, Brian; Visser, Amy; Sanders, Donald; Burns, Ted M.
ABSTRACT Introduction: Mycophenolate mofetil (MMF) is frequently used to treat myasthenia gravis, but there is little information to guide clinicians on the safety of reducing the dose in well‐controlled patients. Methods: This retrospective chart review at 3 institutions identified 92 patients who had undergone MMF taper after achieving either pharmacologic remission or minimal manifestations status. Statistical analysis was performed to assess differences in patient characteristics between patients who had successfully tapered MMF and those who relapsed. Results: Of 92 patients undergoing a taper, 30 relapsed. The relapses were mild, transient, and usually responded to increased MMF dose. MG crisis did not occur. The mean dose at time of relapse was 888 mg/day. Patients with relapses were tapered more quickly (8.4 vs. 62.4 months). Conclusions: Tapering MMF appears safe after years of disease stability. Reducing the dose at a dose of only 500 mg/day every 12 months is recommended. Muscle Nerve52: 211–215, 2015